Impact «Horiotsen» some biochemical blood parameters in lactating sows - Шатохін, П. П.; Супруненко, К. В.; Каришева, Л. П. (Scientific Progress & Innovations, 2016)
The paper presents the results of research on the development and implementation of environmentally friendly practices of veterinary preparations, namely placental able to normalize metabolic processes in tissues and restore the structure and function of organs and body systems. We established that the yard at multiple input of «Horiotsen» increased protein levels on 1,5 % compared to the index of the first days after farrowing and 5,3 % – rate of animals in the control group at 28th day. Glucose increase after the injection in all groups – p<0,001, but in the experimental groups the figure was higher than in the control one by 8,7, 7,0 and 6,1 %. Against the background of hyperphosphatemia content of inorganic phosphorus in the blood sows of 3rd research group at the 28th day was 17 Im% lower than in the control group of sows.